Identification of nitrifying/denitrifying bacteria and their application in the treatment of nitrogenous waste in shrimp aquaculture wastewater with emphasis on brevibacterium strain VCM10 / Sarmila Muthukrishnan - Muthukrishnan, Sarmila (2015)
Management of water quality in aquaculture system is essential. Deterioration of water quality particularly to high concentration of total ammonia nitrogen (TAN) affects the productivity of the aquaculture system. In this study, twenty-one bacterial strains were isolated from shrimp wastewater and assessed for TAN reduction activity. Based on preliminary and secondary screenings, strain VCM5, VCM8, VCM10, VCM11, and VCM12 were selected as potential strains. All the five strains reduced TAN significantly (p < 0.05) and showed positive reduction in nitrate analysis. Of the five strains tested, strain VCM10, exhibited the highest TAN removal (p<0.05, 88.17%) within 5 days. The ability and efficiency of strain VCM10 in reducing TAN investigated in both aerated and agitated culture systems. The results indicated that VCM10 reduced TAN levels in both aerated-cultures (95.61% reduction) and agitated- cultures (75.46% reduction) within five days. The NO2--N concentrations also decreased in both aerated-culture (95.35%) and agitated-culture (29.71%). The NO3—N reduction in the two experiments were 82.57% and 69.14% over 5 days. The COD levels in the aerated-culture system decreased 75.48% from 1491.33 ± 32.67 mg/L on day one to 365.33 ± 44.96 mg/L on day five. The COD levels in the agitated-culture system only decreased by 54.29% from 1474.67± 80.93 mg/L on day one to 674.00 ± 22.12 mg/L on day five. The ability of strain VCM10 immobilised on various substrates to treat wastewater was evaluated. Strain VCM10 colonised substrates showed similar activity but sponge and sand gave significantly higher (p < 0.05) TAN reduction. Strain VCM10 immobilised on sponge and sand showed 88.63% and 88.55% TAN reduction respectively, within three days of treatment. Scanning electron microscope (SEM) studies revealed the benefits of using sponge as a support medium which provides large surface area for bacterial attachment and colonisation. Strain VCM10 immobilised on sponge and sand showed significant (p < 0.05) removal of TAN from 120.86 ± 7.62 mg/L to 0.84 ± 0.10 mg/L (99.03% removal) within 48h after inoculation in a column flow through (CFT) system. However, sponge and sand has the ability to absorb TAN by (21.39%) while nitrification by immobilised strain VCM10 further reduced TAN level (~100%) Phylogeny analysis was performed to identify strain VCM10. Similarity of the obtained 1302bp fragment of 16S rRNA gene in GenBank using BLAST revealed 99% sequence similarity with the 16S rRNA gene sequence of type species Brevibacterium linen DSM20425 (X77451). The 16S rRNA gene sequence of strain VCM10 was deposited in GenBank with the accession number KC912855. Addition to that, preliminary assessment of the efficacy of strain VCM10 was studied. Strain VCM10 gave better survival rate of Artemia larvae (72.6%) compared to the control (without any bacteria) (49.0%) with significant difference (P < 0.01) after six days. Addition to that, the concentration of TAN in treatment vessels reduced significantly (p < 0.05) compared to the control (without any bacteria)